Using mixed reality technique combines multimodal imaging signatures to adjuvant glioma photodynamic therapy - Dong, Jiawei; Wang, Fang; Xu, Yuyun; Gao, Xin; Zhao, Hongtao; Zhang, Jiheng; Wang, Nan; Liu, Zhihui; Yan, Xiuwei; Jin, Jiaqi; Ji, Hang; Cheng, Ruiqi; et al. (Frontiers in Medicine, 2023)
BACKGROUND: Photodynamic therapy (PDT) promotes significant tumor regression and extends the lifetime of patients. The actual operation of PDT often relies on the subjective judgment of experienced neurosurgeons. Patients can benefit more from precisely targeting PDT's key operating zones. METHODS: We used magnetic resonance imaging scans and created 3D digital models of patient anatomy. Multiple images are aligned and merged in STL format. Neurosurgeons use HoloLens to import reconstructions and assist in PDT execution. Also, immunohistochemistry was used to explore the the association of hyperperfusion sites in PDT of glioma with patient survival. RESULTS: We constructed satisfactory 3D visualization of glioma models and accurately localized the hyperperfused areas of the tumor. Tumor tissue taken in these areas was rich in CD31, VEGFA and EGFR that were associated with poor prognosis in glioma patients. We report the first study using MR technology combined with PDT in the treatment of glioma. Based on this model, neurosurgeons can focus PDT on the hyperperfused area of the glioma. A direct benefit was expected for the patients in this treatment. CONCLUSION: Using the Mixed Reality technique combines multimodal imaging signatures to adjuvant glioma PDT can better exploit the vascular sealing effect of PDT on glioma. Keywords: Glioma, Photodynamic therapy, Magnetic resonance imaging, Mixed reality, Hololens